ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA - Retno Utami; Devi Fitria Assifa; Sindhi Nurfatiyah; Cintya Ayu Wulansih; Khabibun Najib; F. Shoufika Hilyana (STKIP Subang, 2024)
The purpose of this research is to analyze the learning difficulties factors of elementary school students in mathematics lessons, and to find out what materials students do not understand in mathematics lessons. This research uses the Systematic Literature Review (SLR) method. The aim of the Systematic Literature Review (SLR) research method is to transmit, review and recognize relevant research so that it is able to answer questions in the specified research. The results of the research show that the factors causing elementary school students' learning difficulties in mathematics learning are that internal factors include (1) Interest, students who are less interested in participating in mathematics learning, plus students in the class are less focused and serious in following the teaching and learning process as per the students' views. always leads to outside the classroom when the teacher explains the material, (2) Factors of students' learning habits, less accurate learning of students who only study when there are tests (3) Factors of students' health, can influence the level of students' concentration in learning mathematics, if the student's body is lacking healthy, it can influence student learning outcomes.